The Rotating Beam Problem in Helicopter Dynamics - Ganguli, Ranjan; Panchore, Vijay; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
The book addresses computational methods for solving the problem of vibration, response, loads and stability of a helicopter rotor blade modeled as a rotating beam with flap or out-of-plane bending. The focus is on explaining the implementation of the finite element method in the space and time domain for the free vibration, aeroelastic response and stability problems. The use of Floquet analysis for the aeroelastic stability analysis of rotor blades is also shown. The contents of the book will be useful to researchers in aerodynamics and applied mechanics, and will also serve well professionals working in the aerospace industry.
Introduction -- Finite element analysis in space -- Finite element in time -- Stability analysis -- Helicopter rotor results.
Keywords: Mechanics, Applied; Continuum mechanics; Aerospace engineering; Astronautics; Engineering Mechanics; Continuum Mechanics; Aerospace Technology and Astronautics